The Influence Of Mix Marketing On Decisions For Use Of Online Transportation Towards Global Competition - Candra Wahyu Hidayat (Publisher Cv. Inara, 2021)
This study aims to determine the effect of Marketing Mix on Decisions on the Use of Transportation Based on Malang City Application. This type of research is quantitative research. The population in this study are consumers who use online transportation services in Malang City area. The determination of sample size in this study uses Ferdinand's theory (2015). The sample in this study was 100 respondents. The sampling technique in this study uses the theory of Non Probability Sampling, which is an unknown sampling technique how much is the probability of each element or member of the population to get a chance to become a sample. Based on existing sources there are two kinds of data sources, namely primary data and secondary data. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that partially the promotion, people, process, and physical Evidence variables significantly influence the decision to use online applications. While the variables of production, price, and place do not significantly influence the decision to use online transportation. Simultaneously, together with produc, price, promotion, place, people, process, and physical Evidence have an influence on the decision to use online transportation.